A Conceptual Management Model of Virtual Project Team in International Companies - Kukytė, Aistė (Vilnius University Open Series, 2021)
Globalisation and technological advancement have an enormous impact on how businesses operate. Technological evolution, economic challenges, and different generations working in one workforce impact businesses to seek flexibility and adopt techniques that support virtual teamwork. In the modern international business environment increasing number of teams that work in virtual environments through project execution, leads to the need for theory and research on how successfully manage virtual project teams. In this paper the analysis of the scientific literature allowed to formulate the definition of a virtual project team, the analysis was able to show the management aspects, which are related to the features of the virtual project team, review of scientific literature also let to disclose the emerging problems faced by managers. These results were used to conceptualise the virtual project team management model in international companies.
Keywords: virtual project team; management of virtual project team; management in international companies